Village Fund Policy Implementation Strategy in Sumedang Regency - Restu Widyo Sasongko; Ummu Salamah; Ikin Sodikin (International Journal of Science and Society, 2021)
According to its goals, the Village Fund Policy is successful if it improves the health of rural people and promotes equitable village growth. The aim of this analysis is to investigate and evaluate the factors that contribute to the successful implementation of the Village Fund policy in Sumedang Regency, as well as the strategies that can be implemented. The researchers used observational research techniques in conjunction with a case study approach. This approach was selected in order to gather reliable data for the purpose of identifying important factors affecting the Village Fund strategy. The findings indicate that a variety of factors contribute to the policy's progress in Sumedang Regency, including the affected priorities, the benefits provided, the required degree of improvement, the role of policymakers and program implementers, the resources deployed, and the power and strategies of the actors involved. Institutional characteristics, as well as conformity and responsiveness. However, it is well established that the resource element has been underutilized, with the village relying entirely on funding sources from the Village Budget, the Village Fund Allocation, and other profit-sharing funds for government administration, growth, and community empowerment.